An extraordinary-performance gradient nanostructured Hadfield manganese steel containing multi-phase nanocrystalline-amorphous core-shell surface layer by laser surface processing. (20th January 2023) - Sun, Wanting; Luo, Jiasi; Chan, Yim Ying; Luan, J.H.; Yang, Xu-Sheng
Highlights: Gradient nanostructured layer on austenitic Hadfield manganese steel was fabricated by laser surface remelting technique. Gradient refinement transits from dislocations activities and twinning in sub-region to three kinds of martensitic transformations, and finally a multi-phase nanocrystalline-amorphous core-shell structural surface. The multi-phase nanocrystalline-amorphous core-shell structural surface with an average grain size of ∼ 8 nm is obtained. The core-shell structural surface exhibits a tensile strength of ∼ 1.6 GPa, a micro-pillar compressive strength of ∼ 4 GPa at a strain of ∼ 8%, and a nanoindentation hardness of ∼ 7.7 GPa. Dislocation activities are kept inside extremely refined nanograins in the multi-phase nanocrystalline-amorphous core-shell structural surface. Abstract: Reducing grain size (i.e. increasing the fraction of grain boundaries) could effectively strengthen nanograined metals but inevitably sacrifices the ductility and possibly causes a strengthening-softening transition below a critical grain size. In this work, a facile laser surface remelting-based technique was employed and optimized to fabricate a ∼600 μm-thick heterogeneous gradient nanostructured layer on an austenitic Hadfield manganese steel, in which the average grain size is gradually decreased from ∼200 μm in the matrix to only ∼8 nm in the nanocrystalline-amorphous core-shell topmost surface. Atomic-scale microstructural characterizations dissected the gradient refinement processes along the gradient direction, i.e. transiting from the dislocations activities and twinning in sub-region to three kinds of martensitic transformations, and finally a multi-phase nanocrystalline-amorphous core-shell structural surface. Mechanical tests (e.g. nanoindentation, bulk-specimen tensile, and micro-pillar compression) were conducted along the gradient direction. It confirms a tensile strength of ∼1055 MPa and ductility of ∼10.5% in the laser-processed specimen. Particularly, the core-shell structural surface maintains ultra-strong (tensile strength of ∼1.6 GPa, micro-pillar compressive strength of ∼4 GPa at a strain of ∼8%, and nanoindentation hardness of ∼7.7 GPa) to overcome the potential strengthening-softening transition. Such significant strengthening effects are ascribed to the strength-ductility synergetic effects-induced extra work hardening ability in gradient nanostructure and the well-maintained dislocation activities inside extremely refined nanograins in the multi-phase nanocrystalline-amorphous core-shell structural surface, which are evidenced by atomic-scale observations and theoretical analysis. This study provides a unique hetero-nanostructure through a facile laser-related technique for extraordinary mechanical performance. Graphical abstract: Image, graphical abstract